Perancangan Motor Bakar Bensin 4 TAK Dengan Daya 8 HP Digunakan Untuk Perontok Padi - Niharman niharman (MAJALAH TEKNIK SIMES, 2020)
Abstract This plan aims to find out a gasoline motor that is produced to be well efficient, data specifications of gasoline motors with motor power of 8.0 HP, motor speed of 2200 Rpm, Diameter x Step 14 cm x 16.8 cm', after planning and this calculation we can find out as follows: Volume cylinder block 230.1 cm , Torsion torque moment 175.3 kg/cm, shaft diameter 5.2 cm. Compression is air pressure which has a very big role in producing engine speed, both temperature and power generated, let us be more careful in planning a motor compression pressure, it is better not to compress too high and not too low, use an appropriate compression system.